2022
DOI: 10.1039/d1ra08555g
|View full text |Cite
|
Sign up to set email alerts
|

What are the prospects for using complexes of copper(ii) and zinc(ii) to suppress the vital activity of Mycolicibacterium smegmatis?

Abstract: New complexes of zinc(ii) and copper(ii) with 2-furoic acid (Hfur), acetic acids and N-donor ligands with the compositions [Zn2(fur)4]n, [Zn2(fur)4(NH2py)2], [Zn(fur)2(neoc)], [Zn(OAc)2(neoc)], and [Cu(fur)2(neoc)(H2O)] were synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 62 publications
(89 reference statements)
2
8
0
Order By: Relevance
“…Nevertheless, complexes 1 , 2 , and 3 showed very good antibacterial activity against MRSA BAA1717 with MIC values of 200, 350, and 450 μg/mL, respectively. Comparing these MIC values with those reported for some model Zn­(II) complexes (MIC = 200–500 μg/mL), one can state that analogous antibacterial activities are observed for the present complexes. In contrast, there are some literature reports on Zn­(II)-based complexes that exhibit relatively lower activity with MIC values of >500 μg/mL , or higher activity with MIC values of <200 μg/mL, , in comparison to the present complexes described in this study. It is noteworthy to mention that control experiments using three zinc salts such as ZnCl 2 , Zn­(NO 3 ) 2 ·6H 2 O, and Zn­(CF 3 CO 2 ) 2 ·H 2 O showed insignificant antibacterial activity (Figure S13, Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…Nevertheless, complexes 1 , 2 , and 3 showed very good antibacterial activity against MRSA BAA1717 with MIC values of 200, 350, and 450 μg/mL, respectively. Comparing these MIC values with those reported for some model Zn­(II) complexes (MIC = 200–500 μg/mL), one can state that analogous antibacterial activities are observed for the present complexes. In contrast, there are some literature reports on Zn­(II)-based complexes that exhibit relatively lower activity with MIC values of >500 μg/mL , or higher activity with MIC values of <200 μg/mL, , in comparison to the present complexes described in this study. It is noteworthy to mention that control experiments using three zinc salts such as ZnCl 2 , Zn­(NO 3 ) 2 ·6H 2 O, and Zn­(CF 3 CO 2 ) 2 ·H 2 O showed insignificant antibacterial activity (Figure S13, Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…As follows from the data in Table 3, complex 3 is the most effective against mycobacteria (MIC = 8 nmol per disk), with comparable activity to Rif (MIC = 5 nmol per disk). Previously obtained results of biological activity for various carboxylate copper(II) complexes indicate that N-donor ligands, being part of the complex, are able to determine (increase or weaken) biological activity [3][4][5][6][7] (Table 3).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…13,26,30 The complexes of 3d-metals with 2-furoic acid (Hfur) studied previously showed bioactivity against mycobacterial strains, along with interesting magnetic and sorption properties. [32][33][34][35][36][37][38][39][40][41] In this work, we focused on the study of the self-assembly of 1-, 2-and 3-D coordination polymers by slow diffusion of a crosslinking ligand solution (1,2-bis(4-pyridyl)ethylene) into solutions of Ni II /Co II furoates in various solvents. Given the apparent simplicity of the suggested approach (no special conditions), it was observed that varying the solvents allowed polymers with various dimensions and structures to be formed.…”
Section: Introductionmentioning
confidence: 99%
“…13,26,30 The complexes of 3d-metals with 2-furoic acid (Hfur) studied previously showed bioactivity against mycobacterial strains, along with interesting magnetic and sorption properties. 32–41…”
Section: Introductionmentioning
confidence: 99%